Physico-Chemical Studies on Some Metal Complexes of Ce(IV), V(IV), Nb(V), Ta(V) and Mo(VI) with Substituted Thioquinazoles Having Thioamide Group - Pandey, R.N.; Sahay, A.N.; P. Sharma, (Mrs.); Kumar, Sanjay; Pathak, A.K. (Asian Journal of Chemistry, 2010)
Complexes of 2-mercapto-3-substituted quinazoline-4-one have been prepared and investigated using Ce(IV), V(V), Nb(V), Ta(V) and Mo(VI). These have the stoichiometries M(QTH)X5 (M = Nb or Ta; X = Cl or NCS), [VO2(PQTH)3Cl], [V2O4(QTH)4(NCS)2], [Ce(PQTH)(H2O)5)(NO3)4 and [MoO2(PQTH)2Cl2]·4H2O (QTH= 2–mercaptoquinazoline-4-one and PQTH = 2-mercapto-3-phenylquinazoline-4-one). Structures of these complexes have been tentatively assigned on the basis of micro-analytical, conductivity, UV, visible, infrared and far-infrared spectral data. All the complexes have octahedral configuration.